Quality of life measurement in hidradenitis suppurativa: position statement of the European Academy of Dermatology and Venereology task forces on Quality of Life and Patient‐Oriented Outcomes and Acne, Rosacea and Hidradenitis Suppurativa. (29th April 2019) - Chernyshov, P.V.; Zouboulis, C.C.; Tomas‐Aragones, L.; Jemec, G.B.; Svensson, A.; Manolache, L.; Tzellos, T.; Sampogna, F.; Pustisek, N.; van der Zee, H.H.; Marron, S.E.; Spillekom‐van Koulil, S.; et al.
Abstract: This paper is organized jointly by the European Academy of Dermatology and Venereology (EADV) Task Force (TF) on Quality of Life (QoL) and Patient‐Oriented Outcomes and the EADV TF on acne, rosacea and hidradenitis suppurativa (ARHS). The purpose of this paper was to present current knowledge about QoL assessment in HS, including data on HS‐specific health‐related (HR) QoL instruments and HRQoL changes in clinical trials, and to make practical recommendations concerning the assessment of QoL in people with HS. HS results in significant quimp that is higher than in most other chronic skin diseases. HS impact in published studies was assessed predominantly (84% of studies) by the Dermatology Life Quality Index (DLQI). There is a lack of high‐quality clinical trials in HS patients where HRQoL instruments have been used as outcome measures. One double‐blind randomized placebo‐controlled trial on infliximab with low number of participants reported significantly better HRQoL improvement in the treatment group than in the placebo group. Well‐designed clinical studies in HS patients to compare different treatment methods, including surgical methods and assessing long‐term effects, are needed. Because of lack of sufficient validation, the Task Forces are not at present able to recommend existing HS‐specific HRQoL instruments for use in clinical studies. The EADV TFs recommend the dermatology‐specific DLQI questionnaire for use in HS patients. The EADV TFs encourage the further development, validation and use of other HS‐specific, dermatology‐specific and generic instruments but such use should be based on the principles presented in the previous publications of the EADV TF on QoL and Patient‐Oriented Outcomes.